Circular RNA protein tyrosine kinase 2 (circPTK2) promotes colorectal cancer proliferation, migration, invasion and chemoresistance. Issue 1 (1st January 2022) - Jiang, Zhipeng; Hou, Zehui; Liu, Wei; Yu, Zhuomin; Liang, Zhiqiang; Chen, Shuang
ABSTRACT: The dysregulated circular RNAs (circRNAs) are linked to progression and chemoresistance in colorectal cancer (CRC). However, the role of circRNA protein tyrosine kinase 2 (circPTK2) in CRC progression and chemoresistance is uncertain. The circPTK2, microRNA (miR)-136-5p, m6A 'reader' protein YTH domain family protein 1 (YTHDF1), β-catenin and cyclin D1 abundances were examined via quantitative reverse transcription PCR or Western blotting. The progression was investigated by cell counting kit-8 (CCK-8), colony formation, transwell and xenograft analysis. The resistance to 5-fluorouracil (5-FU) and oxaliplatin was analyzed via detecting cell viability and apoptosis using CCK-8 analysis and flow cytometry. The binding relationship was examined through dual-luciferase reporter, RNA immunoprecipitation and pull-down analysis. In our study, circPTK2 abundance was enhanced in CRC and associated with liver metastasis, clinical stage and chemoresistance. CircPTK2 knockdown constrained cell proliferation, migration, invasion, resistance to 5-FU and oxaliplatin, and the Wnt/β-catenin signaling. MiR-136-5p was bound with circPTK2 and downregulated in CRC. MiR-136-5p knockdown attenuated the influence of circPTK2 silence on CRC progression and chemoresistance. YTHDF1 was targeted via miR-136-5p and upregulated in CRC samples and cells. MiR-136-5p targeted YTHDF1 to restrain CRC progression and chemoresistance. In addition, we confirmed that circPTK2 silence reduced xenograft tumor growth. In conclusion, circPTK2 interference suppressed CRC proliferation, migration, invasion and chemoresistance via regulating miR-136-5p and YTHDF1. Abbreviations: circRNAs: circular RNAs; CRC: colorectal cancer; circPTK2: circRNA protein tyrosine kinase 2; miR: microRNA; YTHDF1: YTH domain family protein 1; CCK-8: cell counting kit-8; 5-FU: 5-fluorouracil; RIP: RNA immunoprecipitation.